RETURN IN ADOPTION: PENALTIES AND THE EFFECTS CAUSED ON RETURNED CHILDREN AND/OR ADOLESCENTS AND THEIR RIGHTS - Ferreira da Silva, Eliandra (Revista Gênero e Interdisciplinaridade, 2023)
This article has as its objective the issue of devolution in adoption and its effects on children and/or adolescents who have been returned and their rights. We will address the role of the State in cases of return of children and adolescents, who are in foster care institutions, and are going through the adoption process. We will also include in this scientific article the concept of adoption, according to some scholars; we will bring some of the adoption in Brazil; we will explain about the qualification process and the return process and your motivations; the legal responsibility of potential adopters, who return the child and/or adolescent.